Dynamic Low-Carbon Dispatching Method of Power System Based on Improved Carbon Emission Flow Theory - Jiaxing CHEN; Chunling WANG; Chunming LIU (Zhongguo dianli)
At present, power systems are facing great pressure of carbon reduction. With the development of smart grids, the participation of demand-side resources in power-system scheduling can further reduce carbon emissions of power systems. Therefore, this paper proposes a dynamic low-carbon two-stage optimal scheduling method considering demand response in a day-ahead market. In the first stage, the carbon market transaction cost on the power generation side is calculated based on a metering model of dynamic carbon emission of generation units. On this basis, an optimization model for low-carbon economic scheduling of a power system is established to obtain an initial schedule. In the second stage, based on the improved carbon emission flow theory of power systems, the real-time carbon emission and cost of users are calculated. Moreover, demand response with carbon price as a signal is considered to establish a low-carbon economic optimal dispatch model to optimize load distribution to further reduce carbon emission of the system. On this basis, a final schedule can be obtained. Finally, the improved IEEE 14 node system is used as an example to calculate and analyze carbon emissions and total operating cost of the system. The simulation results show that the proposed model and method can reduce carbon emissions of the system, thus verifying their feasibility and rationality.